2022
DOI: 10.3389/fmed.2022.941739
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin as a crucial biomarker in the diagnosis and prognosis of intravenous immunoglobulin resistance and coronary artery lesions in Kawasaki disease: A systematic review and meta-analysis

Abstract: BackgroundEarly identification and treatment are paramount for intravenous immunoglobulin (IVIG) resistance and coronary artery lesions (CALs) in patients with Kawasaki disease (KD). Unfortunately, there is no single crucial biomarker to identify these patients in a timely manner, which makes KD the most common cause of acquired heart disease in children in developed countries. Recently, many studies have focused on the association between serum ferritin (SF), IVIG resistance, and CALs in KD. We thus performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Currently, an increasing number of studies are emerging regarding the diagnostic and prognostic value of PNI in various diseases. A previous meta-analysis investigated the value of PNI in the prognosis of cardiovascular diseases and showed that PNI can independently (17,33,34). In addition, neutrophil-tolymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been confirmed for their discriminative abilities to predict IVIGresistant KD patients in previous reports (35,36).…”
Section: Discussionmentioning
confidence: 95%
“…Currently, an increasing number of studies are emerging regarding the diagnostic and prognostic value of PNI in various diseases. A previous meta-analysis investigated the value of PNI in the prognosis of cardiovascular diseases and showed that PNI can independently (17,33,34). In addition, neutrophil-tolymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been confirmed for their discriminative abilities to predict IVIGresistant KD patients in previous reports (35,36).…”
Section: Discussionmentioning
confidence: 95%
“…Vascular smooth muscle cells (VSMCs) in children with Kawasaki disease can increase ROS levels due to abnormal autophagy processes, activating corresponding cell death pathways and upregulating expression of NLRP3, to exacerbate mitochondrial dysfunction and vascular inflammation [ 217 ]. Studies revealed that serum iron levels are often reduced and serum ferritin levels are abnormally high in patients with KD, and these effects can be mediated by hepcidin treatment [ 218 , 219 ]. Through the combined action of various factors, VSMCs undergo iron overload and death, affecting vascular endothelial integrity.…”
Section: Relevant Clinical Diseasesmentioning
confidence: 99%
“…Patients with this condition experience acute febrile systemic vasculitis, in which their blood vessels become highly inflamed. Although it was already reported that sFT levels are elevated during Kawasaki disease [85], it was also recently shown that sFT may be used in the differential diagnosis between Kawasaki disease and other febrile pathologies, and also in the prognosis of coronary artery lesions in patients with this condition [86,87].…”
Section: Role Of Circulating Ferritin In Health and Diseasementioning
confidence: 99%